Rethinking Education in Pakistan: perceptions,practices,and possibilities - Shahid,Siddiqui
This book review summarizes a book titled "Rethinking Education in Pakistan" that critically analyzes Pakistan's education system and identifies issues like high illiteracy rates, lack of funding for higher education, weak teacher training programs, over-reliance on private tutoring, and curriculum and assessment practices that limit meaningful learning. The book advocates for reforms like improving literacy, increasing education funding, modernizing teacher training, reducing tutoring, and implementing student-centered curriculum and assessment to strengthen Pakistan's education system and promote national development.
Includes bibliography
Keywords: Education -- Pakistan, Education and state -- Pakistan, Educational change -- Pakistan, Non-formal education -- Pakistan